2016
DOI: 10.1177/0960327115608930
|View full text |Cite
|
Sign up to set email alerts
|

Lipid emulsion attenuates apoptosis induced by a toxic dose of bupivacaine in H9c2 rat cardiomyoblast cells

Abstract: The goal of this in vitro study was to investigate the effect of lipid emulsion on apoptosis induced by a toxic dose of bupivacaine (BPV) in H9c2 rat cardiomyoblast cell lines. The effect of lipid emulsion on the decreased cell viability and count induced by BPV or mepivacaine (MPV) in the H9c2 cells was assessed using an 3-(4,5-dimethylthiazole-2-yl)-2,5-diphenyl tetrazolium bromide assay or a cell count assay. The effect of BPV or lipid emulsion combined with BPV on cleaved caspase 3, caspase 8, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
24
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 35 publications
10
24
1
Order By: Relevance
“…Pre-treatment or post-treatment with lipid emulsion in in vitro studies performed using isolated vessels has been demonstrated to reverse or attenuate the vasodilation induced by toxic doses of local anesthetics in a lipid solubility-dependent manner [ 3 7 12 23 ]. In H9c2 cells, lipid emulsion-mediated inhibition of apoptosis induced by a toxic dose of bupivacaine is enhanced compared with that induced by a toxic dose of mepivacaine [ 24 ]. In addition, pre-treatment or post-treatment with lipid emulsion has been shown in in vivo studies to be effective during recovery from cardiac arrest induced by bupivacaine but to have no effect on recovery from cardiac arrest induced by mepivacaine, suggesting that the efficacy of lipid emulsion treatment is partly dependent on the lipid solubility of the local anesthetic [ 25 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pre-treatment or post-treatment with lipid emulsion in in vitro studies performed using isolated vessels has been demonstrated to reverse or attenuate the vasodilation induced by toxic doses of local anesthetics in a lipid solubility-dependent manner [ 3 7 12 23 ]. In H9c2 cells, lipid emulsion-mediated inhibition of apoptosis induced by a toxic dose of bupivacaine is enhanced compared with that induced by a toxic dose of mepivacaine [ 24 ]. In addition, pre-treatment or post-treatment with lipid emulsion has been shown in in vivo studies to be effective during recovery from cardiac arrest induced by bupivacaine but to have no effect on recovery from cardiac arrest induced by mepivacaine, suggesting that the efficacy of lipid emulsion treatment is partly dependent on the lipid solubility of the local anesthetic [ 25 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, pre-treatment or post-treatment with lipid emulsion has been shown in in vivo studies to be effective during recovery from cardiac arrest induced by bupivacaine but to have no effect on recovery from cardiac arrest induced by mepivacaine, suggesting that the efficacy of lipid emulsion treatment is partly dependent on the lipid solubility of the local anesthetic [ 25 26 ]. All of these previous studies indicate that lipid emulsion-mediated recovery from cardiovascular collapse due to local anesthetic toxicity can be partly attributed to lipid emulsion-mediated sequestration of the local anesthetics, which is dependent on their lipid solubility [ 1 3 7 12 23 24 25 26 ]. Similar to previous reports, in the current study, lipid emulsion attenuated vasodilation induced by a toxic dose of bupivacaine ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipid emulsion may also protect myocardial cells form local anesthetic -induced apoptosis. 12 Another proposed mechanisms is a metabolic benefit of lipid emulsion that reverses local anesthetic-induced inhibition of mitochondrial respiration in cardiac tissue. 13 In isolated myocardial mitochondria, the main depressive effect of bupivacaine on the mitochondrial respiratory chain is the inhibition of complex I (nicotinamide adenine dinucleotide [NADH] dehydrogenase).…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis is a crucial physiological cell death process that can be induced by toxic stimuli [25]. Previous studies have shown that T-2 toxin injection can strongly induce cell apoptosis in different tissues, such as thymus, spleen and liver, particularly in the liver [6].…”
Section: Discussionmentioning
confidence: 99%